SEROPREVALENCE OF BRUCELLOSIS AMONG PATIENTS PRESENTING WITH NON - SPECIFIC SYMPTOMS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Malik, Saqib; Sarwar, Iram; Rauf, Abdur; Haroon, Muhammad Zeeshan (Journal of Ayub Medical College Abbottabad, 2018)
Background: brucellosis is one of the prevalent zoonotic disease worldwide. It not only adds to the global burden of disease but also has huge economic impact. Clinical features of human brucellosis are usually vague. This study was carried out to find out the frequency of brucellosis among patients presenting with nonspecific symptoms in hospital setting and to find out risk factors. Methods: Study was carried out in outpatient Medicine Department of Ayub Teaching Hospital Abbottabad for the period of 3 months. Patients presenting with nonspecific symptoms of fever, body aches, myalgias, arthralgia, headache, backache, malaise and insomnia of either gender between the ages of 18-60 years were included in the study through consecutive sampling technique. Blood Samples from patients were sent for screening Brucella antibodies by serum agglutination method. Antibodies were checked for both Brucella abortus and mellitensis. Results: total 70 patients were recruited in the study. Out of these 49 (70%) were found positive for Brucella. These positive Brucella patients were mostly 42 (85.71%) female and majority 35 (71.4%) were in the age group of 21-40 years. In both male and female patients' majority were positive for both species of Brucella. Nonspecific symptoms included Aches, Pains and Myalgia in all the patients with additional symptoms of Malaise in 13 (18.6%), headache 10 (14.3%) and insomnia and fever in 9 (12.9%) each. Majority of the enrolled patients 53 (75.71) gave negative history of using boiled/pasteurized milk in their daily consumption while 17 (24.3%) patients suggested use of boiled/pasteurized milk. Conclusion: A high frequency of human brucellosis was found among patients presenting with nonspecific symptoms, therefore it is recommended that such patients should be screened for brucellosis. Keywords: Brucellosis; Brucella abortus; Brucella mellitensis; Nonspecific symptoms; Zoonosis